К вопросу о возрастных изменениях кожи и ее нервных элементов у овец - Наумова, Н.А. (Вестник зоологии, 1968)
An intraorganic innervation of sheep's skin in ontogenesis is studied extremely insufficiently. In order to study the morphogenesis of the nerve components of sheep's skin in detail, the sheep were examined in an age aspect. The process of complication and transformation of skin morphological components is traced back. It is established that the most intensive innervation is observed in the region of hair roots, which is probably associated with their receptor function.